Modeling the point of use EROI and its implications for economic growth in China. (1st February 2018) - Feng, Jingxuan; Feng, Lianyong; Wang, Jianliang; King, Carey W.
Abstract: Energy return on energy invested (EROI) might be considered a measure of net energy, and most current studies focus on standard EROI (EROIST ). If the energy inputs required to obtain a fuel was extended from a wellhead to the point of use, the energy delivered decreases, and the energy input of delivering the fuel increases. These factors combine to reduce the EROIST to what is referred to as the point of use EROI (EROIPOU ). This study calculates the direct and indirect energy (embodied energy) inputs for energy production sectors (including extraction, processing and delivery) by means of an Input-Output table to calculate China's EROIPOU and the net energies from 1987 to 2012. Based on calculations in this study, the EROIPOU of China's energy production sector declined from 11.01:1 to 5.26:1 between 1987 and 2012. In 1987, the energy production sectors consumed 1 ton standard coal equivalent (TCE) energy inputs for every 10.01 TCE of produce net energy. However, in 2012, this number declined to 4.25. Additionally, this study simulates and forecast economic Gross Domestic Product (GDP) trends in China using net energy production function. The results reveal how declining EROIPOU for Chinese fossil fuels influence China's GDP growth. Highlights: Excessive embodied energy is consumed by the processing of fossil fuels. The EROIPOU trends for Chinese fossil fuels have continued to decline to 5.26:1. The GDP forecasted in this study is lower because of declining EROIPOU .